FACTORS AFFECTING CASH HOLDING ON PROPERTY AND REAL ESTATE COMPANIES - Tanujaya, Martin; Wijaya, Henryanto (International Journal of Application on Economics and Business, 2025)
The purpose of this research is to obtain empirical evidence regarding the influence of financial distress, inflation, institutional ownership, leverage, and firm size on cash holding in property & real estate companies listed on the Indonesia Stock Exchange in 2020 to 2022 period. The sample in this research is 87 samples. with a period of 3 years which has been selected using purposive sampling, certain criteria, and data outlier. This research was proceeded using Microsoft Excel 2019 and Eviews 12 software. The results of this research show that financial distress, institutional ownership, and firm size have a positive effect on cash holding. However, the results found for the variables consist of inflation and leverage have no effects on cash holding.